Optimizing Healthcare Efficiency: The Role of Artificial Intelligence in Medical Records Management - Karri, Hari Krishna; Begum, Ayesha; George, Lina (International Journal of Engineering and Management Research, 2024)
The integration of artificial intelligence (AI) into medical records management is transforming healthcare delivery by optimizing patient care, research, and administrative processes. This research paper explores the multifaceted impact of AI on medical records management, elucidating its benefits, challenges, and future directions. Through a comprehensive analysis, the paper highlights AI's role in automating data extraction and classification, streamlining clinical workflows, and enhancing decision support systems. AI-driven predictive analytics enable proactive intervention and personalized healthcare delivery, further optimizing resource allocation and patient outcomes. However, the adoption of AI in medical records management is accompanied by challenges, including algorithmic biases, data privacy concerns, and interoperability issues. Addressing these challenges necessitates collaborative efforts among stakeholders to ensure ethical, secure, and equitable AI adoption in healthcare settings. Looking ahead, future research may explore advancements in AI technology, such as semantic interoperability and federated learning, to unlock new opportunities for improving healthcare delivery. Through interdisciplinary collaboration and innovative solutions, AI holds the potential to revolutionize medical records management, paving the way for a more efficient, effective, and patient-centered healthcare system.